Think Pair Share Strategy on the Topic of Heart Diseases in the Subject of Aqidah Akhlak - Qohar, Abdul; Hadi, Sofyan; Rofiqur Rahman, Zainur; Syafii, Hafidt Abdulloh Bin (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2025)
This study investigates the effectiveness of the Think-Pair-Share (TPS) strategy in enhancing student learning outcomes in the Islamic Religious Education subject, with a focus on the Aqidah Akhlak topic of Heart Diseases, in Class VI at Madrasah Ibtidaiyah Syarifuddin Lumajang. The research was motivated by persistently low academic performance among students, as evidenced by an average class score below the minimum Learning Achievement Criteria (LAC). Employing a Classroom Action Research (CAR) methodology, the study was conducted over two cycles, each comprising the stages of planning, implementation, observation, and reflection. Findings demonstrate a marked improvement in student engagement and conceptual understanding, with the average score rising from 65.25 in the pre-cycle to 74.31 in Cycle I and 80.19 in Cycle II. Furthermore, the proportion of students meeting the minimum Learning Achievement Criteria increased from 18.75% (3 students) in the pre-cycle to 81.25% (13 students) in the second cycle. These results indicate that the TPS strategy significantly enhances not only students' academic performance but also their active participation in learning. This research contributes to the pedagogical discourse by validating the use of collaborative learning models within religious education contexts, particularly in reinforcing abstract moral and theological concepts for young learners.